2017
DOI: 10.12693/aphyspola.131.406
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic, Elastic and Thermal Properties of Cubic Perovskite-Type SrThO3

Abstract: The electronic structure, elastic, thermal and optical properties of the cubic strontium thorate SrThO3 are calculated using the full-potential linearized augmented plane wave method (FP-LAPW) based on the density functional theory with generalized gradient approximations GGA and local density approximation LDA. The modified Becke-Johnson potential (mBJ) is applied in electronic structure for calculating the energy gap. The obtained results are the Young modulus, shear modulus, the Poisson ratio, isotropic she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In the context of Kleinman parameters, ξ = 0 corresponds to minimizing bond bending and ξ = 1 corresponds to minimizing bond stretching. 70…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of Kleinman parameters, ξ = 0 corresponds to minimizing bond bending and ξ = 1 corresponds to minimizing bond stretching. 70…”
Section: Resultsmentioning
confidence: 99%
“…In the context of Kleinman parameters, x = 0 corresponds to minimizing bond bending and x = 1 corresponds to minimizing bond stretching. 70 It is observed that the Debye temperature and the melting temperature of the perovskite materials decrease as Cl is replaced by Br and I. This trend is also reected in their longitudinal, transverse and average sound velocity.…”
Section: Elastic Propertiesmentioning
confidence: 92%
“…SrTh03 is optimized and the structural parameters are calculated. For optimization process we selected the unit cell volume for the input from previous experimental work [12]. Then we varied the unit cell volume in the neighborhood of the experimental volume.…”
Section: 1structural Parametersmentioning
confidence: 99%
“…The first synthesis of SrThO3 by conventional solid route was reported in 1947 by Marie-Szabo [12]. Recently Subasri et al, have noted the limited thorium oxide solubility in SrO and that the formation of the pure ternary phase is not achieved [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation